Catalytic Combustion‐Type Hydrogen Sensor Using BaTiO3‐based PTC Thermistor. Issue 6 (12th February 2013) - Yuasa, Masayoshi; Nagano, Takahito; Tachibana, Naoki; Kida, Tetsuya; Shimanoe, Kengo; Damjanovic, D.
<x xml:space="preserve">Abstract</x> A catalytic combustion‐type gas sensor using a positive temperature coefficient (PTC) thermistor, which shows a sharp resistance change around Curie temperature, was developed for the detection of hydrogen. La‐doped BaTiO3 (Ba0.998 La0.002 TiO3) was prepared through a solid‐state method and an oxalic acid method. La‐doped BaTiO3 obtained by the oxalic acid method showed improved PTC properties, due to the formation of fine particles, as compared to that prepared with the solid‐state method. The resulting sensor device showed a fairly high H2 sensitivity in the range of 100–1000 ppm. In addition, the H2 sensitivity and response speed were improved by coating a Pt/SiO2 catalyst on the sensor device because the catalytic combustion efficiency of H2 was improved by the catalyst coating.